Interação de níveis de água e densidade de plantas no crescimento e produtividade do Feijão-Caupi, em Teresina, PI - de Oliveira, Simone Raquel Mendes; de Andrade Júnior, Aderson Soares; Ribeiro, Valdenir Queiroz; de Brito, Ramilos Rodrigues [UNESP]; Carvalho, Marcus Willame (My University, 2015)
The objective of this study was to evaluate the effect of levels of water, plant density and their interaction on growth (dry matter and leaf area) and yield of cowpea (Vigna unguiculata L. Walp.). The experiment was carried out at the experimental area of Middle- North Embrapa in Teresina city, Piauí-Brazil from July to September 2012 in a Ultisol soil. A randomized block experimental design was used with four replicates. Treatments were applied in a 5 x 4 factorial design and 5 levels of irrigation as factors: 393.53; 340.34; 300.50; 260.39 and 201.73 mm applied through an irrigation system by conventional sprinkler, and four plant densities: 150,000; 200,000; 250,000; 300,000 plants ha-1. A significant interaction between irrigation levels and plant density was found in all study parameters except for dry matter. Leaf area, grain yield, number of pods per plant, pod weight, pod yield, pod length and hundred grain weight had maximum values of 1,301.89 cm2; 1,668.86 kg ha-1; 2.24; 2,248.16 kg; 1,873.45 kg ha-1; 18.70 cm and 22.72 g, which were reached using the following water depths: 367.86; 390.88; 393.53; 393.53; 393.53; 348.40 and 322.63 mm associated with densities of : 188,000; 241,000; 110,000; 254,000; 254,000; 223,000 and 300,000 plants.ha-1, respectively.
Interaction between levels of water and plant density on growth and yield of Cowpea in Teresina, PI
Keywords: Density; Intraspecific competition; Water stress